GERAKAN BERSIH PANTAI BERSAMA SEBAGAI PENDUKUNG PARIWISATA HALAL DI PESISIR PANTAI TELUK KECAMATAN LABUAN - E. Egriana Handayani; Dedeh Jubaedah; Lambang Satria Himmawan; Cahyanti Cahyanti; Kholifatus Solihah; Fatonah Islamiyah (International Journal Mathla’ul Anwar of Halal Issues, 2022)
According to Presidential Regulation No. 83 of 2018 on Handling Marine Waste, Marine Waste is garbage that comes from land, water, and coastal bodies that flow into the sea or garbage that comes from activities in the sea. While plastic waste is garbage that contains polymer compounds. This plastic waste has become the largest component of marine debris. Marine debris is found in all marine habitats, ranging from densely populated areas to remote locations that are untouched by humans; from coastal and shallow water areas to deep sea troughs. The density of marine debris varies from location to location, influenced by human activities, aquatic or weather conditions, the structure and behavior of the Earth's surface, the entry point, and physical characteristics of the waste material. Halal lifestyle has become a trend of need in the world. Halal tourism is part of the tourism industry that provides tourism services. By referring to islamic rules, in addition to the trend of halal tourism the majority of Muslims around the coastal village of Labuan subdistrict bay make an important factor that must be considered in the halal lifestyle by a Muslim. This research aims to invite the community around TPI Bay and Labuan Subdistrict Batako to participate in the Garbage Collection Movement to be used as Halal Tourism on the Coast of Labuan District Bay in 2021.